2011
DOI: 10.1177/1744629511430772
|View full text |Cite
|
Sign up to set email alerts
|

Health inequalities experienced by children and young people with intellectual disabilities

Abstract: This literature review aimed to synthesize evidence on the prevalence and determinants of health conditions and impairments among children and young people with intellectual disability in the United Kingdom. Several databases were systematically searched for studies conducted with children under the age of 18 living in the United Kingdom and published in 2010-11. Evidence from a 2002 and a 2010 literature review on health inequalities among individuals of all ages with intellectual disability was also reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
80
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 48 publications
2
80
0
Order By: Relevance
“…This indicates that increased BMI in this population of SOI participants is not likely due to high muscle mass attributed to their participation in sport. The relatively high proportion of participants with a weight status outside the normal range may both reflect poorer health of the SOI children and youth but also expose them to conditions associated with a less favourable BMI status in the future (Allerton et al, 2011;Emerson and Hatton, 2014;World Health Organization, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that increased BMI in this population of SOI participants is not likely due to high muscle mass attributed to their participation in sport. The relatively high proportion of participants with a weight status outside the normal range may both reflect poorer health of the SOI children and youth but also expose them to conditions associated with a less favourable BMI status in the future (Allerton et al, 2011;Emerson and Hatton, 2014;World Health Organization, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The research to date has shown that children and adolescents with ID have numerous disturbances concerning both cognitive and motor functioning [1,2]. They are less active than their healthy peers [3,4], prone to overweight and obesity [5,6], and mostly lead a sedentary way of life [7,8]. Balance control deficits observed in adolescents with ID, as compared to their healthy schoolmates [9], difficulties with the ability to concentrate on two or more things at a time [10], and problems with planning and organising movements [11] may increase the risk of accidental falls [12] and limit their independence in activities of daily living (ADLs) [13].…”
Section: Introductionmentioning
confidence: 99%
“…Children with an intellectual disability (ID) have significant deficiencies in intellectual and adaptive functioning (American Association on Intellectual and Developmental Disabilities 2013) and exhibit an increased incidence of several other disorders or impairments compared with children without an ID (Allerton, Welch, and Emerson 2011). In addition, families with a child having an MID are more frequently of a lower socioeconomic status (Strømme and Magnus 2000;Emerson, Einfeld, and Stancliffe 2010;Olsson et al 2015).…”
Section: Introductionmentioning
confidence: 99%